(فلسفة المنهج التجريبي عند الحسن ابن الهيثم) (Journal of Humanitarian and Applied Sciences, 2023)
The study in area refers to the role of Muslim scholars and their concerms the demo, his scientific philosophy since the foot, and they are considered the first basis for that era Time, especially when lbn al-Haytham (in writlng) scens (which translated some. His topics are experienced in the observation , which depends on the observation, and the arrogance, and Sun Laws , and thus filled This scientific achievement , the minds of Greece and lndia cwestern books and therefore did not meet this activity Scientific pud :But studied lbn al-Hailham chemistry mathematics engineering and philosophy Through those sciences he explained his theory , in the knowledge of the eyes and the movement of obiects Falling mutated light and light , and making the experimental approach depends on lnduction: The decision made the researcher, such a study because it is more pruning Ban shot for the world .Muslim scholars have the role and appreciate such sciences and maintitng our Arab collections.